Successful management of a tooth with canal obstruction using "cold ceramic" - Jalil Modaresi; Zahra Almodaresi; Rahele Mousavi; Alireza Mirzaeeian; Said Abbas Sadat Hosseini (Wolters Kluwer Medknow Publications, 2021)
One of the causes of treatment failure is calcification in the canal pathway, which prevents complete access to proper working length, and one of the most difficult and challenging cases of root canal treatment has been reported. In some cases, the dentist will not be able to open the calcified canal. Therefore, the prognosis of root canal treatment in these cases has been reported poor, and the dentist will offer a plan for possible treatments, including tooth extraction or apical surgery. The presented case is one example of those cases with a periapical lesion, which as a temporary treatment, the pulp chamber was filled with cold ceramic. This material, which is an MTA-like (Mineral Trioxide Aggregate) bioceramic with proper sealing ability, has been introduced as a root-end filling material. After 6 years of which the patient returned, he did not express any pain or discomfort during these 6 years. Furthermore, in radiograph that was taken, periapical lesion relative healing and bone regeneration were amazingly seen.